Optimization of Trunk Phase Difference for Seeking Maximum Bidirectional Green Wave Bandwidth. Issue 1 (1st January 2023) - Zhang, Jie; Zhang, Junyou; Zhu, Qinglin; Luo, Yuqiu; Lv, Fengfei; Gao, Han
Abstract: This paper first analysis the shortcomings of the existing traditional numerical solution algorithm to solve the two-way green wave bandwidth problem, then improves the traditional numerical solution algorithm, constructs the objective function, proposes a trunk phase difference optimization method to seek the maximum two-way green wave bandwidth, constructs the model and solves it using Lingo optimization software, which can overcome the disadvantages of artificially fixed speed and common signal period and the lack of connection between green wave speed and common signal period. It can overcome the disadvantages of artificially fixed speed and common signal period and the lack of connection between green wave speed and common signal period, and optimize the signal period, phase difference, green signal ratio and green wave speed simultaneously. Meanwhile, the simulation analysis by VISSIM software verifies that the method can significantly reduce the stopping delay and improve the intersection capacity.